Developing low cost harvesting tool using ergonomics concept for oil palm fresh fruit bunch harvesters in Malaysia: a case study - Mohd Tamrin, Shamsul Bahri; Mohd Yusoff, Irwan Syah; Mat Said, Aini; Ng, Yee Guan; Mori, Ippei (International Ergonomics Association, 2015)
Harvesting fresh fruit bunch activities is high risk and hazardous task that lead to musculoskeletal disorders (MSD) among harvesters. Work situation and the current hand tools to harvest FFB identified as the main contributing factors in increasing MSD. The objective of this study is to design and develop a low cost harvesting tool based on ergonomics principles in order to reduce ergonomics risk and improve the health condition of the harvesters. A cross-sectional study was done in 12 oil palm plantations in the southern part of peninsular Malaysia. 273 harvesters were purposively selected based on the inclusion criteria to participate in this study. A translated Nordic Questionnaire was used to determine the prevalence of MSD. The harvester’s body posture while performing task was recorded using RULA. The association between MSD and the perception of the current harvesting tool was determined using Chi square test and Binary Logistic Regression analysis. Selective anthropometric dimension (width palms and internal diameter hand grip) and chisel tool dimension were taken to determine the severity of mismatch between current and proposed chisel with the hand anthropometry of the harvesters. Significant risk factors and suggestion for improvement by the harvesters were utilized as parameters in designing the new low cost harvesting tool. Design principles based on User Centered Design using SolidWorks 2007. To evaluate the effectiveness new design, RULA analysis using CATIA software in the first phase and the second phase involved prototype fabrication and field test using electromyogram was conducted. Result showed, 78.0% had complaints of MSD at the upper and lower back during the last 12 month and 75.5% reported MSD due to harvesting activities. The effect of using the current harvesting tool (chisel) was redness (85.3%) followed by blister (83.2%). 85.3% of the harvester felt that their current chisel is heavy and 49.0% slipped their hand more than twice monthly due to slippery. Binary logistic regression showed that the risk of developing MSD was 18.2 times higher when the harvester is in awkward position compared to those in neutral position. Those who use the current chisel of less than a year had 5.7 times higher for obtain MSD compared to those who had used the chisel of more than a year. There is high mismatch between the current tools with the proposed chisel. RULA simulation showed that the current design categorized as high risk in developing MSD (score 7) compared to the new proposed design with the score of 3. Field test results showed that the new model prototype able to reduce the score action level to 2. As a conclusion, the study showed that the existing harvesting tool is one of the major risk factor for both health and safety of the harvester. The new harvesting tool able to reduce the need to bend while harvesting and thus increasing the productivity of FFB for each harvester.